« Automation and the Worker: A Study of Social Change in Power Plants » - Fortin, Gérald (Relations industrielles / Industrial Relations, 1961)
The article reviews the book, "Automation and the Worker: A Study of Social Change in Power Plants," by Floyd C. Mann and L. Richard Hoffman.